Factors associated with poor adherence to haart in patients with HIV during the COVID-19 pandemic: Factores asociados a mala adherencia al targa en pacientes con VIH durante la pandemia por la COVID-19 - Rodríguez Díaz, David Rene (2024)
Introduction: In the COVID-19 pandemic, the fear of contagion and the risk of poor evolution were conditions that circumscribed HIV-infected patients, potentially influencing adherence to HAART (A-HAART). Objective: To determine the factors associated with poor adherence to HAART (PA-TARGA) in patients with HIV during the COVID-19 pandemic in a hospital in northern Peru during April-October 2021. Material and Methods: A study was developed cross-sectional analytical study in 162 patients with a confirmed diagnosis of HIV infection on HAART. To establish A-HAART, the Morisky-Green-Levine Test was used. The association between sociodemographic, personal/family factors of COVID-19, health, and PA-HAART was evaluated using the Pearson Chi-square test, considering statistical significance for a p value < 0.05. The risk statistic was the Odds ratio (OR) > 1. Results: The prevalence of PA-HAART was 32%, the mean age 45.8±8.3 and 44.6±7.3 years (with poor and good adherence to HAART), predominantly male. Factors associated with PA-HAART were living alone (p=0,036, OR:3,1), personal history of COVID-19 (p=0,027, OR: 2,42), history of a close relative with COVID-19 (p =0,038, OR 3,42), depression (p=0,036, OR: 2,18) and comorbidity (p=0,027, OR: 2,21). Conclusion: In patients with HIV, living alone, a personal history of COVID-19, a history of a close relative with COVID-19, depression and presenting comorbidity are factors associated with PA-HAART.